THE STUDY OF WHO’S THEORY TO NUMBER OF POSYANDU TARAP VISITS TO INCREASE D/S OF INFANT–TODDLERS COVERAGE - Ifroh, Riza Hayati; Susanti, Rahmi; Winanda, Wenny (Preventif : Jurnal Kesehatan Masyarakat, 2018)
Background & Objective: Maternal participation is one of the supporting factors and indispensable inmonitoring the growth of infants and babies. This is reflected in the comparison of the number of childrenweighed with all children in the region or called the concept of D/S and involvement of parents visitingposyandu. The purpose of this study is to analyze the factors that influence the visits of mothers who haveinfants or toddlers to Posyandu Tarap in order to increase the number D / S through the WHO theoryapproach. This research is an analytic observation research with cross sectional approach. Materials andMethods: The sample that entered as the respondent in this research is the mother who recorded in dataposyandu Year 2017-2018. Results: The number of visit to Posyandu Tarap on average 2 times during last 4months. The average of respondents knowledge is 14.95 and the average of respondents attitude is 43.45. Asmany as 90% of respondents have family support to Posyandu Tarap. In addition, 90% of respondents weremotivated to visit Posyandu Tarap to get information about infant and toddlers health, 95% of respondentsconsidered that distance of building with Posyandu Tarap is very close. Conclusion: There is 1 causalfactor from 7 research variables that influence mother visit to posyandu to weigh her baby that is mothermotivation in doing visit to Posyandu Tarap.